Competition, facilitation and the Allee effect. Issue 4 (25th September 2012) - Lutscher, Frithjof; Iljon, Tzvia
<x xml:space="preserve">Abstract</x> Individuals of different species may interact in many different ways, such as competition, mutualism, or predation, to name but a few. Recent theory and experiments reveal that whether an interaction is beneficial or detrimental to the dynamics of a population often depends on species densities and other environmental factors. Here, we explore how, for suitable densities, facilitation may arise between two competing species with an Allee effect. We consider two different mechanisms for the Allee effect: 1) plant species with obligate insect pollination, and 2) generalist predation. In the first case, a second plant species, competing for nutrients, may have a facilitative effect by attracting more pollinators. In the second case, another potentially competing species may serve to satiate the same generalist predator and thereby have a facilitative effect. We explore three aspects of facilitation in each of the two systems. The focal species may benefit from the presence of a 'competitor' if it experiences 1) the removal of the Allee threshold, 2) a lowering of the Allee threshold, or 3) an increase in carrying capacity. We find that the latter two effects occur in both study systems whereas the first only occurs for the generalist predation system but not for the plant‐pollination system. We give precise conditions on when such a facilitative effect can be expected. We also demonstrate several unexpected outcomes of these two‐species interactions with multiple steady states, such as obligate co‐occurence; we draw parallels to the dynamics of species known as 'ecosystem engineers', and we discuss implications for conservation and management.